A Praxis of Gayatri Spivak’s “Aesthetic Education” Using Arundhati Roy’s “The God of Small Things” as a Reading in Philippine Schools - Pellano, Seneca Nuñeza (The Nordic Journal of Aesthetics, 2017)
Presented as a “speculative manual on pedagogy,” this article seeks to provide praxis to Spivak’s Aesthetic Education in the Era of Globalization (2012) using Arundhati Roy’s The God of Small Things (1997) as a reading in Philippine schools. Its aim is to envision pedagogical ways in which a foreign literary text is introduced into a culturally distant setting, thereby prompting educators – the “supposed trainers of the mind” – to resolve: (1) How does one educate aesthetically? (2) How do we imagine the performance of aesthetic education in local classrooms? In demonstrating a theory and its form, the paper first explores Spivak’s conception of aesthetic education and then adapts it in a specific case: in Philippine classrooms where learners are confronted by a literary work of the Other – particularly, Arundhati Roy’s The God of Small Things. Aesthetic education, as a theoretic idea, is visualized and imaginatively performed through its capacity to realize an “epistemic revolution” happening in local classrooms worldwide.